EFEKTIFITAS PIJAT OKETANI TERHADAP BENDUNGAN ASI PADA IBU POSTPARTUM DI RSB.MASYITA MAKASSAR - jama, fatma; S, Suhermi (Universitas Islam Negeri Alauddin Makassar, 2019)
Exclusive breastfeeding is influenced by several factors, including breast milk does not immediately come out on the first day after childbirth, the mother feels the milk comes out a little, the difficulty of the baby in sucking, the condition of putting breast milk and the promotion of breast milk substitute. The conditions in the field indicate that the success of early breastfeeding is also influenced by the condition of the mother and baby. working mothers and low knowledge of mothers and families about the benefits and correct ways of breastfeeding. The application of oketani massage to post partum mothers is still rarely done because usually mothers only do regular breast massage. Oketani massage is a management skill to overcome the problem of lactation such as inadequate breast milk production, breast swelling, octane massage will cause the breasts to become soft, supple and the areola will become elastic, the lactiferous duct and the nipple also become elastic. The research design used was Quasi Experimental with a pre-test and post-test design. This study only used one group, namely the intervention group without the control group to see the effectiveness of the ASI dam in the intervention group. The sampling technique used was consecutive sampling, the sample in this study were 15 postpartum mothers The results of this study found that all postpartum mothers after doing Oketani massage therapy experienced changes in ASI dam results from the T-test analysis obtained a mean value = 4,800, SD = 1.46 and p value = 0,000 <= 0,05, indicating that Oketani massage therapy effective in changing ASI dams in post partum mothers. Conclusion from this study that the incidence of effective ASI dams can be overcome with Oketani massage